On Some Classes of Invariant Submanifolds of \((k,μ)\)-Contact Manifolds (Journal of Informatics and Mathematical Sciences, 2017)
In this paper, we study invariant submanifolds of \((k,μ)\)-contact manifolds. We consider pseudoparallel, 2-pseudoparallel, Ricci-generalized pseudoparallel, 2-Ricci-generalized pseudoparallel submanifolds of \((k,μ)\)-contact manifolds. Further, we search for the conditions \(\mathcal{Z}(X,Y)·σ = 0\) and \(\mathcal{Z}(X,Y )·\bar{ abla}σ =0\) on invariant submanifolds of \((k,μ)\)-contact manifolds, where $\mathcal{Z}$ is the concircular curvature tensor.
Keywords: Invariant submanifold; \((k; μ)\)-contact manifold; Totally geodesic; Pseudoparallel; Ricci-generalized pseudoparallel